If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2y-12)/(3y-12)=0
Domain of the equation: (3y-12)!=0We multiply all the terms by the denominator
We move all terms containing y to the left, all other terms to the right
3y!=12
y!=12/3
y!=4
y∈R
(2y-12)=0
We get rid of parentheses
2y-12=0
We move all terms containing y to the left, all other terms to the right
2y=12
y=12/2
y=6
| 8w+15=-17 | | 6(u-6)-6=-3(-6u+9)-6u | | 1.2x=64 | | q/11=30 | | 7(x-1)+2(3x+7)=3(4x+1) | | x2-5x+150=0 | | 0.2h–2.4=0.8 | | 2a+4(-4a-8)=-9(-4a+4)-8 | | y/15=11 | | 10+1⁄2x=14 | | y.13=6+y | | 6x+9=3(x+2 | | –6b+4=–7b | | (23-y)^2+y^2=289 | | 17.5=y7 | | 15x+31=9x-11 | | ?x18=45 | | 1/8(t-7)=-7 | | y=27-9 | | 105n-83/20(130-12.5n)=210 | | r-7-5-6= | | Y=1997x+12 | | 1÷9^x=3^-x÷3×81^x | | 32(x+2.32=114.24 | | 9.25x+6=15.5x+11 | | (2x+3)*4-9x=23 | | 6w+7w1/2-20=0 | | 2-20+65k=103 | | 5/3m=-18 | | 9x=45,x+ | | W-2x5=40 | | 10-3a=52 |